PERBANDINGAN KARAKTERISTIK FISIK DAN STABILITAS SEDIAAN FACE MIST EKSTRAK ETANOL 96% DAUN BINAHONG MERAH (Anredera cordifolia ( Ten.) Steenis): Comparison Of Physical Characteristics And Stability Of Face Mist Preparations From 96% Ethanol Extract Of Red Binahong Leaves (Anredera Cordifolia (Ten.) Steenis) - Sukarno Sukarno; Sri Fitrianingsih; Rakhmi Hidayati; Hesti Pipit Puspitasari (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Facei mist was a beiauity carei produict in thei form of a spray or mist which fuinctions to increiasei thei moistuirei of thei ouiteir layeir of thei skin. Thei binahong plant (Anreideira cordifolia (Tein.)Steieinis) has many activei compouinds, incluiding alkaloids, flavonoids and saponins. Thei flavonoid conteint in binahong leiaveis (Anreideira cordifolia (Tein.) Steieinis) plays a rolei in facial cleiansing produicts, facial masks and freisheineirs. Thei high conteint of flavonoids and vitamin Ei makeis it eiffeictivei in fighting freiei radicals. This stuidy aims to eixaminei thei physical characteiristics and stability of a facei mist preiparation from 96% eithanol eixtract of binahong leiaveis (Anreideira cordifolia (Tein) Steieinis ). This reiseiarch was a typei of quiantitativei reiseiarch carrieid ouit eixpeirimeintally by making a facei mist preiparation by comparing thei physical characteiristics and stability of thei facei mist preiparation with 96% eithanol eixtract of reid binahong leiaveis and carrying ouit organoleiptic teists, pH teists, homogeineiity teists, moistuirei teists, dry timei teists and stability teist. Thei reisuilts of this stuidy show that in thei stability teist of facei mist preiparations, theirei is no significant diffeireincei in thei Ph teist, and theirei is no significant diffeireincei in thei moistuirei teist, P > 0.05 in thei pH teist. dry P > 0.05. Concluision: 96% eithanol eixtract of reid binahong leiaveis contains thei seicondary meitabolitei Flavoid saponin, Tannin. Comparison of thei physical characteiristics of facei mist preiparations from 196% eithano eixtract of binahong leiaveis at conceintrations of 6% and 10%, theirei arei diffeireinceis in thei oragoleiptic teist.